2004
DOI: 10.1007/s00253-004-1744-x
|View full text |Cite
|
Sign up to set email alerts
|

Continuous acetonitrile degradation in a packed-bed bioreactor

Abstract: A 20-l packed-bed reactor filled with foamed glass beads was tested for the treatment of acetonitrile HPLC wastes. Aeration was provided by recirculating a portion of the reactor liquid phase through an aeration tank, where the dissolved oxygen concentration was kept at 6 mg/l. At a feeding rate of 0.77 g acetonitrile l(-1) reactor day(-1), 99% of the acetonitrile was removed; and 86% of the nitrogen present in acetonitrile was released as NH3, confirming that acetonitrile volatilization was not significant. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Continuous flow column system of wastewater is a well-established method for remediation of wastes. Furthermore, some studies of large-scale or pilot-scale continuous flow column system with immobilized cells have been successfully used for the treatment of urban and industrial wastewaters containing various contaminants (e.g., acetonitrile, phenol) [22,28,49,51]. In this study, a continuousflow column system has been designed to increase the efficiency of biological treatment systems by (1) allowing greater organic loads, (2) minimizing production of sludge waste by-products, and (3) increasing process stability and resistance to shock load- ing.…”
Section: Propionitrile Biodegradation Using Al and Ct Immobilized Celmentioning
confidence: 99%
See 2 more Smart Citations
“…Continuous flow column system of wastewater is a well-established method for remediation of wastes. Furthermore, some studies of large-scale or pilot-scale continuous flow column system with immobilized cells have been successfully used for the treatment of urban and industrial wastewaters containing various contaminants (e.g., acetonitrile, phenol) [22,28,49,51]. In this study, a continuousflow column system has been designed to increase the efficiency of biological treatment systems by (1) allowing greater organic loads, (2) minimizing production of sludge waste by-products, and (3) increasing process stability and resistance to shock load- ing.…”
Section: Propionitrile Biodegradation Using Al and Ct Immobilized Celmentioning
confidence: 99%
“…Some researchers also demonstrated that the increased mechanical strength and durability for performing the aerobic and anaerobic biodegradation using cellulose triacetate as a microbial carrier [23,27]. Because of its high removal efficiency, biological treatment of wastewater using immobilized cell systems have been applied for practical application [23,[28][29][30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1): a flat plate and a tubular photobioreactor with the algal-bacterial biofilm attached onto 4-8 mm Poraver ® foamed-glass beads [13], a flat plate and a tubular photobioreactor with the biofilm attached onto the bioreactor walls, an algal-turf reactor shallow open pond [14] with the biofilm attached to the reactor base, and a column photobioreactor with suspended algal-bacterial biomass and no biomass retention (chemostat operation). The main characteristics of each photobioreactors are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The exploitation of immobilised bacterial systems has received considerable attention because bacteria in biofilms are more resilient to environmental insults they therefore offer an opportunity to treat more concentrated wastes streams. A biofilm containing a novel Comamonas species in a packed bed reactor demonstrated maximum acetonitrile degradation of 1 g l )1 d )1 (Manolov et al 2005). Immobilised systems also offer the potential to treat gaseous waste, R. ruber immobilised in a synthetic silicon polymer was used to treat gaseous acrylonitrile.…”
Section: Future Applications Of Biological Cyanide Degrading Systemsmentioning
confidence: 99%